Free-living predatory cheyletid mites (Acariformes: Cheyletidae) from Cat Tien National Park, Vietnam - Khaustov, Alexander A.; Salavatulin, Vladimir M.; Tsurikov, Sergey M.; Thinh, Nguyen Van; Khaustov, Vladimir A. (Zootaxa, 2024)
The free-living predatory mites of the family Cheyletidae of the Cat Tien National Park (Vietnam) are reviewed. Females of two monotypic genera, Vietocheyla subiasi gen. and sp. nov., Paracheletogenes mirabilis gen. and sp. nov., and all active stages of a new species Cheletogenes vietnamiensis sp. nov. are described. Four species, Cheletomimus (Hemicheyletia) bakeri (Ehara, 1962), Ch. (H.) gracilis Fain, Bochkov and Corpuz-Raros, 2002, Ch. (H.) chui (Tseng, 1977), and Tutacheyla robusta Corpuz-Raros, 1972 are recorded from Vietnam for the first time.